AGRICULTURAL EMERGENCY: IDENTIFYING RISK BASED ON AGRICULTURAL HEALTH NURSING - Suhari Suhari; Mashuri Mashuri; Zainal Abidin (LPPM Politeknik Kesehatan Kerta Cendekia, 2021)
Background: Lumajang Regency has the potential for disaster and agriculture that can trigger daily emergencies, especially for farmers. Nurses have an important role in overcoming integrated emergency problems related to agriculture. Objectives: The aim of this study was to identify the threats, vulnerabilities, and capabilities of farmers in integrated emergency management based on agricultural nursing. Methods: This study used a descriptive quantitative design through integrated emergency risk identification of farmers based on agricultural nursing. This research was conducted in agriculture and plantations in the Lumajang area over five months between 1st August to 31st December 2018. Participants in this study were farmers and plantations who were willing to be participants who were selected by cluster sampling as many as 357 respondents. Results: The integrated emergency risk of agricultural nursing-based farmers in Lumajang Regency was in the high category. Farmers who do not have employment insurance occupy the very high vulnerability category. The danger of contact with chemicals belongs to the category of emergencies with large financial losses. The ability to get counseling about first aid during an accident is still low. Conclusion: The integrated emergency risk (threats and vulnerabilities) of farmers in Lumajang Regency was still high and the ability of integrated emergency management of farmers based on agricultural nursing was still low. Reducing the emergency risk of integrated farmers based on agricultural nursing is urgently needed by increasing the capacity of farmers and reducing threats and vulnerabilities in agricultural areas.